Prevalence and determinants of pregnancy termination for childbearing women using the modified Poisson regression model: a cross-sectional study of the Tanzania Demographic and Health Survey (TDHS) 2022 - Sizwe Vincent Mbona; Retius Chifurira; Bonginkosi Duncan Ndlovu; Anisha Ananth (BMC Public Health)
Abstract Background Termination of pregnancy continues to be one of the major public health problems. The prevalence and determinants associated with pregnancy termination among women from low-middle income countries such as Tanzania have previously not been thoroughly investigated. Therefore, this study aims to explore the prevalence and determinants associated with pregnancy termination among Tanzanian women. Methods Data for this study was extracted from the 2022 Tanzania Demographic and Health Survey (TDHS). A total of 15,254 women aged 15–49 years, clustered in selected enumerated areas, participated in the survey. A modified Poisson regression model with sampling weights was used to find the factors that are associated with pregnancy termination. Results The prevalence of pregnancy termination was 14.3% (95% CI: 13.81–14.75%). Our findings reveal that several factors are significantly associated with pregnancy termination. In particular, women’s age, level of education, marital status, history of pregnancy losses, wealth status, attempt to delay or avoid getting pregnant outside the ideal birth spacing, and recent internet use, total children ever born, desire for more children, were significantly associated with pregnancy termination. Women who reside in rural areas, those covered by health insurance and those using contraceptives had a significantly lower likelihood of terminating pregnancy compared to their counterparts. Conclusions The findings highlighted that the prevalence of terminating pregnancy is alarming in Tanzania, signaling a significant public health challenge. To address the concerning rates of pregnancy termination, the government of Tanzania and other institutions are advised to enhance the accessibility and quality of healthcare services for women, particularly in rural and underserved areas. Bridging socio-economic inequalities and removing geographic barriers to healthcare access will ensure women receive timely and adequate support.